Avifaunal diversity and water quality analysis of an inland wetland - Sonal, Deshkar; Jagruti, Rathod; Geeta, Padate (Journal of Wetlands Ecology, 2011)
The key physical and chemical parameters of one of the major habitats for birds - the wetlands are known to influence congregation of migratory and resident species of birds. The present study deals with the interactions between these abiotic factors and bird diversity of one such pond in semiarid zone of Gujarat, India. The pond was visited twice in a month. During each visit waterfowl census was carried out and water samples were also collected to document changes in physico-chemical parameters over the seasons. The aggregation of birds in the area is mainly related to the increase in migratory population of birds during winter. The variations in bird aggregations as well as physico-chemical factors are discussed. Key Words: Abiotic factors; Gujarat; physico-chemical parameters; semi-arid zone; waterfowl; wetland DOI: 10.3126/jowe.v4i0.4151 Journal of Wetlands Ecology, (2010) Vol. 4, pp 1-32